Pengaruh Kepedulian Sosial dan Kejelasan Standar Operasional Prosedur Terhadap Keputusan Tanggap Cepat Relawan Pada Bpbd Kota Tangerang Selatan - Fatimah Zahra; Sigit Purnomo (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the influence of social concern and the clarity of Standard Operating Procedures (SOP) on the rapid response decision-making of volunteers at the Regional Disaster Management Agency (BPBD) of South Tangerang City. The research employed a quantitative method with an associative approach. The population consisted of active volunteers of BPBD South Tangerang City, with a sample of 92 respondents selected using a purposive sampling technique. Data were collected through questionnaires, while data analysis techniques included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The results of the study indicate that partially, the Social Concern variable (X1) does not have a significant effect on Volunteers' Rapid Response Decisions (Y), as evidenced by a t-value of -1.162 and a significance level of 0.248 > 0.05. Meanwhile, the SOP Clarity variable (X2) has a positive and significant effect on Volunteers' Rapid Response Decisions (Y), as indicated by a t-value of 7.857 and a significance level of 0.000 < 0.05. Simultaneously, Social Concern and SOP Clarity have a significant effect on Volunteers' Rapid Response Decisions, as demonstrated by an F-value of 30.905 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) of 0.410 indicates that 41.0% of the variation in Volunteers' Rapid Response Decisions can be explained by Social Concern and SOP Clarity, while the remaining 59.0% is influenced by other factors outside the scope of this study. Based on the findings, it can be concluded that the clarity of SOP is the most dominant factor in improving the rapid response decision-making of BPBD South Tangerang City volunteers. Therefore, BPBD should continuously enhance volunteers' understanding and implementation of SOPs through training programs, simulation exercises, and periodic evaluations to improve the effectiveness of volunteer responses in emergency situations.